Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1177/0961203309104865
|View full text |Cite
|
Sign up to set email alerts
|

Colour Doppler ultrasound of the ocular circulation in patients with systemic lupus erythematosus identifies altered microcirculatory haemodynamics

Abstract: We assessed whether quantitative analysis of Doppler flow velocity waveforms is able to identify subclinical microvascular abnormalities in SLE and whether eigenvector analysis can detect changes not detectable using the resistive index (RI). Fifty-four SLE patients with no conventional cardiovascular risk factors, major organ involvement or retinopathy were compared to 32 controls. Flow velocity waveforms were obtained from the ophthalmic artery (OA), central retinal artery (CRA) and common carotid artery (CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 43 publications
2
4
0
Order By: Relevance
“…In this study, changes were identified in waveforms from a large artery (carotid) in addition to those recorded from the microvasculature (ophthalmic and central retinal arteries); however, the differences were not independent of blood pressure and other confounding factors. This highlights the importance of recording the flow velocity signal in close proximity to the microvascular bed, and supports previous observations [38].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, changes were identified in waveforms from a large artery (carotid) in addition to those recorded from the microvasculature (ophthalmic and central retinal arteries); however, the differences were not independent of blood pressure and other confounding factors. This highlights the importance of recording the flow velocity signal in close proximity to the microvascular bed, and supports previous observations [38].…”
Section: Discussionsupporting
confidence: 91%
“…The results from this study support previous findings demonstrating changes in the OA waveform that may be quantified using spectral analysis techniques, but not by the RI, the conventional measure of downstream vascular resistance [23]. More recently, our group has shown that frequency domain analysis, but not RI identifies ocular microcirculatory changes in SLE [38].…”
Section: Controlsupporting
confidence: 88%
“…Time-frequency domain analysis such as the WT reported in this paper describes the component frequencies that make up any particular waveform. There is no direct correlation between certain frequencies and obvious features such as notches on the waveform [14,15,16,19,20]. …”
Section: Discussionmentioning
confidence: 99%
“…Frequency-domain analysis incorporates the entire waveform data and extracts information from blood flow velocity waveforms not achieved through the use of established time-domain parameters such as the RI and PI [14,16]. Frequency-domain analysis has also been shown to be superior to conventional time-domain analysis in detecting microvascular abnormalities in patients with diabetes and autoimmune diseases [14,15,16]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation